The field investigation of the influence of deep excavation construction fence on the mechanical and strength characteristics of soil - ر. مانغوشيف; أ. اوسوكين; حرفوش وائل; و. اديجويهان (Latakia University Journal -Engineering Sciences Series, 2024)
In the course of excavating a thick layer of soft, weak soil in St. Petersburg, Russia, instabilities were encountered in a 21 m long sheet pile excavation fence made of AU Arcelor 18. In light of the rather large depth (12 m) and areal extent (150 m by 80 m) of the excavation, such instabilities presented a significant challenge for the geotechnical engineers. The stability of the sheet pile was increased by constructing vertical and horizontal diaphragms in close proximity by jet grouting. This process can, however, alter the properties of the foundation soil in the vicinity of the excavation fence. To better ascertain how such properties can potentially be altered, excavations involving similar soils from neighboring building were simulated using the PLAXIS finite element program. This paper reviews the results of soil property tests performed in conjunction with the construction of the aforementioned large excavation, as well as the neighboring buildings. The need for continuous monitoring of geotechnical conditions using the methods of static sounding, so as to assess the zone of construction influence and to forecast the mutual influence of the structure being constructed on the surrounding buildings, is discussed.